Hiperealitas Virtual Influencer Lentari Pagi di Instagram - Azzahra, Jihan; Christin, Maylanny (UMSU, 2025)
The development of technology in the Industry 4.0 era has given rise to artificial intelligence (AI), one example of which is virtual influencers. Virtual influencers are an advancement from real human influencers, supported by technological developments. This study discusses how artificial intelligence produces content that creates experiences nearly indistinguishable from reality in the world of social media, specifically Instagram. The objective of this research is to understand how artificial intelligence generates content that increasingly blurs the line between reality and virtual experiences on Instagram. The research method employed is descriptive qualitative, with data collection techniques including literature studies, interviews, and observations of the Instagram account of the virtual influencer Lentari Pagi. The findings of this study indicate that the virtual influencer Lentari Pagi can create experiences that are hard to distinguish from reality through AI-generated content. Lentari Pagi portrays herself as a real individual and convinces her followers that she can perform activities typically done by humans, thus creating a representation that mimics real-world processes and systems.